Phase Iia Randomized Placebo-Controlled Clinical Trial to Evaluate the Efficacy of Bromhexine in Combination with Standard Therapy in the Early Treatment of Covid-19 in Primary Care Patients; [Ensayo Clínico Aleatorizado de Fase Iia Controlado Con Placebo Para Evaluar la Eficacia de la Bromhexina en Combinación Con la Terapia Estándar en el Tratamiento Temprano de la Covid-19 en Pacientes de Atención Primaria] - Reyes-Parada, M; Renard, G; Ampuero-Llanos, E (Sociedad Medica de Santiago, 2024)
The continuous appearance of SARS-CoV-2 variants with both increased transmission and immune evading potential, in addition to the reluctance of some populations to be vaccinated, supports the search for alternative treatments to protect against the viral infection consequences. Bromhexine is a well-known, over-the counter, expectorant which have garnered interest for the potential prevention and treatment of COVID-19. Aim: To evaluate the efficacy of oral bromhexine in patients with mild to moderate symptomatic active SARS-CoV-2 infection. Methods: A randomized, placebo-controlled clinical trial assessing the effectiveness of oral bromhexine in outpatients with active SARS-CoV-2 infection. Adult patients diagnosed with active SARS-CoV-2 infection (n= 36) were randomly assigned (1:1) to receive bromhexine or placebo, with both groups also receiving standard care. The primary efficacy endpoint was viral load reduction (day 4 vs. baseline), while reductions of a series of COVID-19 clinical symptoms were considered as secondary endpoints. Results: No differences in the viral load at different times after the initiation of treatment were observed. In addition, no differences between groups were detected in most of the clinical symptoms evaluated. Remarkably, a significant decrease in the percentage of patients with cough was observed at days 5-7 in the bromhexine group, an effect that was not apparent in the group receiving a placebo. Conclusions: Since coughing is one of the primary forms of transmission for SARS-CoV-2, the observed reduction of coughing might be highly beneficial, particularly for patients living in crowded, poorly ventilated, or confined environments. © 2024 Sociedad Medica de Santiago. All rights reserved.